The associations between diet-induced inflammation and the improvement or worsening of hepatic steatosis and fibrosis: a longitudinal analysis of RaNCD cohort study - Mohammad Sedighi; Amir Saber; Amir Bagheri; Saba Hazratian; Yahya Pasdar; Farid Najafi; Mehdi Moradinazar; Davood Soleimani (Nutrition & Metabolism)
Abstract Background Persistent inflammation plays a crucial role in the pathogenesis of metabolic dysfunction–associated steatotic liver disease (MASLD). We aimed to scrutinize the associations of diet-induced inflammation with the improvement or worsening of hepatic steatosis and fibrosis in MASLD. Methods This longitudinal study involved 2,537 participants from the Ravanser Non-Communicable Disease (RaNCD) cohort (2015–2023). Dietary intake was assessed using the 118-item food frequency questionnaire (FFQ), and diet-induced inflammation was determined using the dietary inflammatory index (DII). The AST to platelet ratio index (APRI) and Fibrosis-4 (FIB-4) were used as confirmed predictive indicators for hepatic fibrosis and the hepatic steatosis index (HSI) was used for hepatic steatosis. Results Adherence to an inflammatory diet independently increases the risk of worsening hepatic steatosis (RR:1.39; 95%CI: 1.02–1.93; P-value: 0.04) and reduces the risk of improving hepatic steatosis (RR: 66; 95% CI: 0.48–0.98; P-value: 0.01) compared to an anti-inflammatory diet. The DII scores did not show any connection to hepatic fibrosis, as determined by FIB-4 (β: − 1.08; 95%CI: − 2.43 to 0.27; P-value: 0.12) and APRI (β: 0.22; 95%CI: − 1.51 to 1.95; P-value: 0.80). Conclusions These results underscore the importance of dietary composition in managing hepatic steatosis and highlight the need for further research to explore the mechanisms underlying these associations.